Prevalence and determinants of post-acute sequelae after SARS-CoV-2 infection (Long COVID) among adults in Mexico during 2022: a retrospective analysis of nationally representative dataResearch in context - Omar Yaxmehen Bello-Chavolla; Carlos A. Fermín-Martínez; Daniel Ramírez-García; Arsenio Vargas-Vázquez; Luisa Fernández-Chirino; Martín Roberto Basile-Alvarez; Paulina Sánchez-Castro; Alejandra Núñez-Luna; Neftali Eduardo Antonio-Villa (Elsevier, 2024)
Summary: Background: Post-acute sequelae after SARS-CoV-2 infection (PASC) remains a concerning long-term complication of COVID-19. Here, we aimed to characterize the epidemiology of PASC in Mexico during 2022 and identify potential associations of covariates with PASC prevalence using nationally representative data. Methods: We analyzed data from the 2022 Mexican National Health and Nutrition Survey (ENSANUT) from 24,434 participants, representing 85,521,661 adults ≥20 years. PASC was defined using both the National Institute for Health and Care Excellence (NICE) definition and a PASC score ≥12. Estimates of PASC prevalence were stratified by age, sex, rural vs. urban setting, social lag quartiles, number of reinfections, vaccination status and periods of predominance of SARS-CoV-2 circulating variants. Determinants of PASC were assessed using log-binomial regression models adjusted by survey weights. Findings: Persistent symptoms after SARS-CoV-2 infection were reported by 12.44% (95% CI 11.89-12.99) of adults ≥20 years in Mexico in 2022. The most common persistent symptoms were fatigue, musculoskeletal pain, headache, cough, loss of smell or taste, fever, post-exertional malaise, brain fog, anxiety, and chest pain. PASC was present in 21.21% (95% CI 19.74-22.68) of subjects with previously diagnosed COVID-19. Over 28.6% of patients with PASC reported symptoms persistence ≥6 months and 14.05% reported incapacitating symptoms. Higher PASC prevalence was associated with SARS-CoV-2 reinfections, depressive symptoms and living in states with high social lag. PASC prevalence, particularly its more severe forms, decreased with COVID-19 vaccination and for infections during periods of Omicron variant predominance. Interpretation: PASC remains a significant public health burden in Mexico as the COVID-19 pandemic transitions into endemic. Promoting SARS-CoV-2 reinfection prevention and booster vaccination may be useful in reducing PASC burden. Funding: This research was supported by Instituto Nacional de Geriatría in Mexico.